Thematic Based PJOK Module Development - Zuraidah Nurhadi; Budi Valianto; Eva Faridah; Indra Kasih (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
This study aims to describe the validity of thematic-based PJOK modules for grade IV elementary schools in odd semesters. The research used is the development (Research & Development), Borg and Gall. The research subjects were 18 PJOK teachers from three sub-districts in Medan City, namely (Medan Johor, Medan Selayang, and Medan Deli), as well as 3 expert validators.A questionnaire is used to collect information. The module category was found to be very practical to use, with an average score of 95% based on the results of the three expert validations. The first PJOK teacher validated the results with an average score of 94 percent. and the average score on the wider cohort test is 92 percent. and operational field trials yielded results with an average score of 92 percent. From the three seasoned professionals (PJOK teachers) an average score of 92.6% was obtained, with a very decent category. This shows that the thematic-based PJOK module is valid for use by teachers in PJOK learning for grade IV elementary schools.